Core–Satellite Mesoporous Silica–Gold Nanotheranostics for Biological Stimuli Triggered Multimodal Cancer Therapy. (6th June 2018) - Jin, Ronghua; Liu, Zhongning; Bai, Yongkang; Zhou, Yongsheng; Gooding, J. Justin; Chen, Xin
Abstract: A core–satellite nanotheranostic agent with pH‐dependent photothermal properties, pH‐triggered drug release, and H2 O2 ‐induced catalytic generation of radical medicine is fabricated to give a selective and effective tumor medicine with three modes of action. The nanocomplex (core–satellite mesoporous silica–gold nanocomposite) consists of amino‐group‐functionalized mesoporous silica nanoparticles (MSN‐NH2 ) linked to L‐cysteine‐derivatized gold nanoparticles (AuNPs‐Cys) with bridging ferrous iron (Fe 2+ ) ions. The AuNPs‐Cys serve as both removable caps that control drug release (doxorubicin) and stimuli‐responsive agents for selective photothermal therapy. Drug release and photothermal therapy are initiated by the cleavage of Fe 2+ coordination bonds at low pH and the spontaneous aggregation of the dissociated AuNPs‐Cys. In addition, the Fe 2+ is able to catalyze the decomposition of hydrogen peroxide abundant in cancer cells by a Fenton‐like reaction to generate high‐concentration hydroxyl radicals (·OH), which then causes cell damage. This system requires two tumor microenvironment conditions (low pH and considerable amounts of H2 O2 ) to trigger the three therapeutic actions. In vivo data from mouse models show that a tumor can be completely inhibited after two weeks of treatment with the combined chemo‐photothermal method; the data directly demonstrate the efficiency of the MSN–Fe–AuNPs for tumor therapy. Abstract : A core–satellite nanotheranostic agent with pH‐dependent photothermal property, pH‐triggered drug release, and H2 O2 ‐induced catalytic medicine is fabricated to give a selective and effective tumor medicine with three modes of action. This nanoplatform can completely inhibit the tumor growth after use, indicating that the novel trimodal photochemotherapy is a promising theranostic for efficient cancer treatment.